A Mutual Appreciation of Differences: My Conversation with Philip M. Bromberg. Issue 2 (3rd April 2022) - Kluft, Richard P.
Abstract: Concepts from emerging relational/intersubjective perspectives elaborate a definition, understanding, and clinical approach to dissociation consistent with their paradigms. They cast new light upon dissociation as a long underappreciated and often overlooked (primarily characterological) defense. While some embrace the extension of these ideas into work with the formal dissociative disorders, others think that that this development risked conveying both an incomplete picture of dissociation as a defense and contributing to a potential misunderstanding of these conditions and their treatment. This report summarizes conversation between the late Philip M. Bromberg and the author of this paper as they worked to clarify and reconcile their divergent perspectives on several relevant issues.